Effects of a tennis training program adapted for cardiac rehabilitation of patients with low risk acute coronary syndrome - Díaz Casasola, César; Fuentes García, Juan Pedro; Menayo Antúnez, Ruperto; Barca, J.; Gómez, J. J. (KRONOS, 2010)
At present, slightly healthy ways of life (sedentary lifestyle, unhealthy food, stress, etc.) prevail in our society. Concurrently,rates of cardiovascular diseases causes alarm since they constitute the first cause of death in developed countries.Considering this social problem, we have conducted a study that aims to define the effects of a cardiac rehabilitationtraining program, based on the practice of tennis, in patients with acute coronary syndrome. Our objective wasto determine the technical level achieved after the training program and to specify if improvements were maderegarding accuracy comparing the pre-test and the post-test.The sample consisted of a group of six patients, of average age 53.57 ± 4.68. Systematic observation was used as anassessment tool. The shot technique and accuracy achieved were filmed and subsequently analysed with the helpof observational grids previously validated. The statistical analysis of the results showed significant differences (p =.001and p =.005) in both shot technique and shot accuracy after the training program.